Approaches to Post-Intensive Care Syndrome: Nursing Point of View - Nagaya, Yoshiyuki; Kaga, Mari (Archives of Clinical and Biomedical Research, 2018)
Health professionals have been aware of the incidence of post-intensive care syndrome (PICS) for some time. However, there has not been a clear or definitive way of administering treatment or nursing care to help patients suffering from PICS in their recovery. This paper suggests some ideas for the care of patients from the nursing point of view.